Off-pump coronary artery bypass prevents visceral organ damage. (13th March 2014) - Bierbach, Benjamin; Bomberg, Hagen; Pritzer, Hartmut; Prabhu, Sudesh; Petzina, Rainer; Kempski, Oliver; Horstick, Georg; Cremer, Jochen; Hoffmann, Grischa
Abstract: OBJECTIVES: Visceral malperfusion after coronary artery bypass grafting (CABG) results in high morbidity and mortality. This study was designed to evaluate the effect of CABG performed by surgical techniques on visceral perfusion and function. METHODS: Pigs ( n = 28) were studied in four groups: I. Sham; II. Off-pump coronary artery bypass grafting (OPCAB): 1 h stabilizer with 40 min intracoronary shunt; III. Extracorporeal circulation (ECC): 1 h ECC with 40 min aortic cross-clamping and cardioplegic arrest; IV. Impella: 1 h left ventricular blood-pump support and stabilizer with 40 min intracoronary shunt. A left internal mammary to left anterior descending coronary artery bypass was performed in Groups II–IV. All animals were observed for a further 240 min. During the experiment haemodynamics, creatinine clearance, intestinal fatty acid binding protein (iFABP), pancreatic (lipase and amylase) and liver enzymes (α-glutathione s-transferase, glutamate-oxaloacetate transaminase (GOT), gamma-glutamyl transferase (GGT), glutamate dehydrogenase and glutamate-pyruvate transaminase (GPT)) were measured. Visceral perfusion (VP) was assessed in both kidneys, intestine, pancreas, liver and spleen with 15 µm fluorescent microspheres. RESULTS: During OPCAB surgery, VP decreased slightly. Renal functional parameters, iFABP, pancreatic and liver enzymes remained unchanged. ECC and Impella led to significantly reduced renal, pancreatic and intestinal blood flow ( P < 0.05). Creatinine clearance, pancreatic and liver (GPT, GGT) enzymes were significantly decreased only after ECC ( P < 0.05). ECC and Impella resulted in a significantly increased iFABP level ( P < 0.05). GOT was elevated significantly after surgery in Groups II, III and IV ( P < 0.05). CONCLUSIONS: CABG with ECC or Impella leads to impaired visceral blood flow and function. OPCAB minimizes these procedure associated alterations.